2-(Bipiperidin-1-yl)-5-(nitroaryl)-1, 3, 4-thiadiazoles: Synthesis, evaluation of in vitro leishmanicidal activity, and mechanism of action. Issue 16 (15th August 2019) - Mojallal-Tabatabaei, Zahra; Foroumadi, Parham; Toolabi, Mahsa; Goli, Fereshteh; Moghimi, Setareh; Kaboudanian-Ardestani, Sussan; Foroumadi, Alireza
Graphical abstract: Highlights: Synthesis of six different derivatives of 5-(nitroheteroaryl)-1, 3, 4-thiadiazole. The assessment of in vitro anti-leishmanial activity. IIc andIIa were the most active compounds against L. major. The level of ROS was increased in treated cells. IIa andIIc induce apoptosis in promastigotes. Abstract: The development of novel leishmanicidal agents that are capable of being replaced by the available therapeutic options has become a priority. In the present study, the synthesis and leishmanicidal activity of a series of 5-(nitroheteroaryl-2-yl)-1, 3, 4-thiadiazole derivatives are described. All compounds appeared to be potent anti-leishmanial agents against both promastigote and amastigote forms of Leishmania major ( L. major) . Amongst the synthesized compounds, 2-([1, 4′-bipiperidin]-1′-yl)-5-(5-nitrofuran-2-yl)-1, 3, 4-thiadiazole (IIa ) and 1-(5-(1-methyl-5-nitro-1 H -imidazole-2-yl)-1, 3, 4-thiadiazol-2-yl)-4-(piperidine-1-yl) piperidine (IIc ) are the most effective. Infection index was statistically declined in the presence of all compounds. The analysis of redox-related factors revealed that exposure of L. major cells toIIa andIIc led to an increase in reactive oxygen species (ROS). Furthermore, two compounds were able to increase ROS and NO levels in infected macrophages in a dose-independent manner. In addition, we showed that these compounds induced cell death in promastigotes. Altogether, our results indicated the anti-leishmanial potential ofIIa andIIc is mediated by apoptosis through an imbalance in the redox system resulting in the elevation of ROS. This new class of compound seems to hold great promise for the development of new and useful anti-leishmanial agents.